AFM imaging, fractal analysis and in vitro cytotoxicity evaluation of Zn(II) vs. Cu(II) porphyrins. (August 2015) - Socoteanu, Radu; Anastasescu, Mihai; Dobrescu, Gianina; Boscencu, Rica; Vasiliu, Georgiana; Constantin, Carolina
Highlights: Porphyrinic complexes with Cu(II) and Zn(II) as metallic ion are studied. Atomic force microscopy was used to investigate the morphology pattern. Correlation function and variable length scale methods were used in fractal analysis. Cytotoxicity was evaluated using U937 cell line. Abstract: A pair of unsymmetrical porphyrinic complexes with Cu(II) and Zn(II) as metallic ion are studied first time by a combination of atomic force microscopy experiments with complex fractal analysis. In view of a possible use of these metalloporphyrins in diagnosis and photodynamic therapy of cancer, the morphological and structural investigations were coupled with cytotoxicity evaluation using U937 cell line. Atomic force microscopy coupled with fractal analysis was proved to be a useful tool to predict the self-similarity domains, in terms of morphology patterns with specific fractal dimensions which may be used to predict a better bio-activity in potential medial applications. Our data point out that the investigated compounds did not alter membrane integrity, but acted as cytostatics at higher concentrations and prolonged incubation time. We highlighted that the investigated porphyrinic structures might interfere with cellular LDH, particularly after 24 h incubation.